Сторона обвинувачення як суб’єкт доказування при вирішенні питання про арешт майна - Гловюк Ірина Василівна; Гловюк Ирина Васильевна; Glovyuk Iryna V. (My University, 2016)
Статтю присвячено дослідженню проблем нормативної регламентації та практики реалізації доказування при вирішенні питання про арешт майна у контексті сторони обвинувачення як суб’єкта доказування. На основі аналізу положень КПК України, судової практики охарактеризовано роль сторони обвинувачення як суб’єкта доказування при вирішенні питання про арешт майна, запропоновано зміни та доповнення до ст.ст. 132, 173 КПК України.

Статья посвящена исследованию проблем нормативной регламентации и практики реализации доказывания при решении вопроса об аресте имущества в контексте стороны обвинения как субъекта доказывания. На основе анализа положений УПК Украины, судебной практики охарактеризована роль стороны обвинения как субъекта доказывания при решении вопроса об аресте имущества, предложены изменения и дополнения в ст.ст. 132, 173 УПК Украины.

The article is dedicated to the study of legal regulation and practice of proving when disposing the issue of property attachment in the aspect of prosecution as a subject of proving. Based on CPC provisions and court practice, the participation of prosecution as a subject of proving in disposing the issue of property attachment was examined. It was proved that in determination of prosecution’s role in criminal procedural proving during the property attachment it is crucial to distinguish the local facts in proof depending on the purpose of attachment; the recovery of obtained illegitimate profit from the entity is considered as a separate purpose of attachment. The burden of proving such circumstances as concealment, damaging, deterioration, destruction, transformation and exclusion of property shall be placed upon the prosecution. Investigator or/and prosecutor takes a part in examination of the motion by investigative judge or court. The defense substantiates the statements of motion by giving things and documents, initiation of hearing any witness or examination any materials that have significant meaning for deciding the issue of property attachment. Such statement as «complex of reasons or reasonable suspicions» is doubtful in the aspect of qualitative grounds which are necessary for making the decision of property attachment; such statement as «complex of sufficient reasons or reasonable suspicions» seems to be more logical. For improvement the process of proving in examination of enforcement measures to ensure criminal proceedings generally and attachment of property particularly it was proposed to withdraw the statement of subclause 3 clause 2 art.173 of CPC of Ukraine: «if attachment of property is imposed under the statements of subclause 3,4 clause 2 art. 170 CPC of Ukraine»; clause 5 art. 132 of CPC of Ukraine was proposed to express in follow edition: «during examination of the enforcement of measures to ensure criminal proceedings, parties to criminal proceedings and other participants should present to investigating judge or court evidence on circumstances to which they refer».
Гловюк І. В. Сторона обвинувачення як суб’єкт доказування при вирішенні питання про арешт майна / І. В. Гловюк // Вісник кримінального судочинства. - 2016. - №3. – С. 18-25.
Keywords: слідчий суддя; суд; арешт майна; слідчий; прокурор; локальний предмет доказування; следственный судья; суд; арест имущества; следователь; прокурор; локальный предмет доказывания; investigative judge; court; attachment of property; investigator; prosecutor; local facts in proof